TRAPPED IN THE WHEEL OF SAMSARA. THE WORKS OF SAMUEL BECKETT IN THE LIGHT OF CHOSEN ELEMENTS OF THE FAR EAST PHILOSOPHY. - Gryszkiewicz, Anna (Porównania, 2019)
The author confronts Samuel Beckett’s works with selected concepts of Eastern philosophy. The article expands previous research conducted by Piotr Dariusz Klimczak, contained in his thesis “Theatre of the Absurd. Thanathic Trilogy” and is based on the hypothesis that Beckett’s dramas and novels, as ones which arise on the existential philosophical discourse background, can in an indirect way transmit the basic doctrines of Buddhism and Hinduism, though not without some shifts to the original philosophical system. The author, unlike in Lidan Lin and Pavneet Kaur studies which consider Artur Schopenhauer as the main East West connecting link, locates the basis of his research in a three-person scheme, Beckett – Heidegger – Suzuki, according to which Eastern philosophy, especially the teachings of the Zen school, could reach Beckett as an echo of the influence of Heidegger’s ontology.